KAJIAN STATUS KUALITAS AIR SUNGAI RIAM KANAN Studi Kasus Sungai Riam Kanan Di Desa Awang Bangkal Kecamatan Karang Intan Kabupaten Banjar - Lestari Fatria Wahyuni; Mijani Rahman; Fadly H. Yusran; Eka Iriadenta (Universitas Lambung Mangkurat, 2011)
This study was executed to analyze the water quality of Riam Kanan River, especially at Awang Bangkal village, Karang Intan District, Banjar County. The analysis using the purposive sampling method was done at four stations; at a station before any activities involved in the river and surroundings, at after the presence of aquaculture activities, at after the presence of some settlements, and at after some activities of coral sand mining and aquaculture. The incite and laboratory analysis result for 13 parameters of the fourth stations showed that there were 3 parameters (BOD, COD, and DO) at Station I-III and 5 parameters (TSS, BOD, COD, DO and oil/fat) at Station IV which have exceeded the first grade water quality standard according to PPRI No. 82 2001 and the decree of South Kalimantan Governor No.05 2007. Based on the status of water quality standard, it can be determined that the Riam Kanan River, especially Awang Bangkal Village, Karang Intan District, Banjar County was included in moderate- contaminated, whereas at the station after the coral sand mining was heavy contaminated. It can be concluded that in general, the Riam Kanan River, especially Awang Bangkal Village, Karang Intan District, Banjar County was unfit to be used as drinking water.